First results from the measurements of atmospheric Maxwell currents at an Indian station, Maitri, Antarctica - Panneerselvam, C.; Jeeva, K.; Nair, K.U.; Selvaraj, C.; Gurubaran, S. (My University, 2001)
An instrument to measure the atmospheric air-Earth current, the fundamental parameter of the global electric circuit was commissioned at an Indian station, Maitri, Antarctica in December 1999. The horizontal long wire antenna is used as. a sensor for picking up charges that constitute various currents collectively called the Maxwell current. The objective of the present work is to understand the response of the experimental setup to various atmospheric electrical and meteorological conditions and to explore the possibilities of detecting the global DC component believed to be the result of global thunderstorm activity. During the fairweather conditions the diurnal variation closely follows the trend of the Carnegie curve.
Keywords: Global electric ciruit; Maxwell currents; Maitri; Antarctica; GEC